Evaluation of managers’ perspectives on secondary dental care in Endodontic in Minas Gerais, Brazil (Research, Society and Development, 2023)
The aim of this study was to evaluate the perceptions of Municipal Oral Health Coordinators (MOHCs) of endodontic services in Dental Specialty Centers (DSCs) of Minas Gerais, Brazil. A questionnaire was sent to the MOHCs of municipalities that had DSCs. Endodontic productivity data were collected from the Health System database. Descriptive analysis and Spearman’s correlation were performed (p≤0.05). Most cities had one DSC operating (92.4%) with two endodontists (30.3%). Endodontic treatments (ETs) were performed exclusively in a DSC (87.9%). There were referral protocols for primary to secondary care in endodontics in 87.9%. Most of the DSCs had a target (84.8%); 60.6% followed the targets recommended by the Brazilian Ministry of Health (MofH), but 53.0% complied with the goal in less than 25% of the months. Technological auxiliary resources for endodontics were not present in 42.0% of the DSCs. Positive correlation was found between the number of dentists who performed ETs in DSCs with fulfillment of monthly targets (p=0.029), and a negative correlation between the availability of technological resources for the fulfillment of monthly targets (p=0.012). Some MOHCs were unaware of the principles of the MofH, suggesting that management measures and targets should be reevaluated.